2001
DOI: 10.1002/mmnd.4800480104
|View full text |Cite
|
Sign up to set email alerts
|

A new electrentomoid psocid (psocoptera) from the Cretaceous amber of Alava (Northern Spain)

Abstract: Manicapsocidus enigmaticus gen. n. sp. n. is described from some amber inclusions of the Cretaceous deposit of Alava (Northern Spain). It is provisionally placed into the extant family Manicapsocidae. This new species shares some features with the Compsocidae and possesses some unusual exclusive characteristics. The discovery of this new species will probably have a certain impact on the interpretation of the phylogeny of the Electrentomoid Psocoptera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The study of psocids from Spanish amber was initiated by Baz & Ortuño (2000), who erected the family †Archaeatropidae and later studied †Empheriidae and Manicapsocidae (Troctomorpha). Five psocid species from Spanish amber have been identified to date (all of them from Álava amber) (Baz & Ortuño 2000, 2001 a , b ): Archaeatropos alavensis Baz & Ortuño, 2000, Empheropsocus arilloi Baz & Ortuño, 2001 b , Empheropsocus margineglabrus Baz & Ortuño, 2001 b , Manicapsocidus enigmaticus Baz & Ortuño, 2001 a and Preempheria antiqua Baz & Ortuño, 2001 b . More than 100 psocids from Spanish amber are pending investigation, most of them from Álava amber.…”
Section: Infraorder Family Genus and Species Type Locality Age Notesmentioning
confidence: 99%
“…The study of psocids from Spanish amber was initiated by Baz & Ortuño (2000), who erected the family †Archaeatropidae and later studied †Empheriidae and Manicapsocidae (Troctomorpha). Five psocid species from Spanish amber have been identified to date (all of them from Álava amber) (Baz & Ortuño 2000, 2001 a , b ): Archaeatropos alavensis Baz & Ortuño, 2000, Empheropsocus arilloi Baz & Ortuño, 2001 b , Empheropsocus margineglabrus Baz & Ortuño, 2001 b , Manicapsocidus enigmaticus Baz & Ortuño, 2001 a and Preempheria antiqua Baz & Ortuño, 2001 b . More than 100 psocids from Spanish amber are pending investigation, most of them from Álava amber.…”
Section: Infraorder Family Genus and Species Type Locality Age Notesmentioning
confidence: 99%
“…Libanomphientomum nudus is Lower Cretaceous in age, older than the Albian taxa currently attributed to the Manicapsocidae or to the Compsocidae (Baz & Ortuño 2001 ;Nel & Waller 2007 ); thus, it is the oldest Amphientometae. It shares with the Upper Cretaceous amphientomid genus Proamphientomum Vishniakova, 1975 the presence of a forked anal vein in the hind wing, which could be a plesiomorphic character.…”
Section: Discussionmentioning
confidence: 88%
“…Amber is a superb medium for the fossilization of fragile or ganisms, preserving even the most delicate structures of small arthropods (Alonso et al, 2000). Recent studies on Alava amber confirmed the presence of numerous biological inclusions, includ ing many new species of insects (e.g., Arillo and Mostovski, 1999;Arillo and Nel, 2000;Arillo and Subias, 2000;Baz and Ortuno, 2000, 2001a, 2001bSzadziewski and Arillo, 1998;Wa ters and Arillo, 1999), in addition to cryptogamic plant remains and indeterminate leaf impressions preserved on the surface of pieces of amber. A set of avian feathers have even been found, including a superb fragment of a contour feather.…”
Section: Materials a N D Methodsmentioning
confidence: 99%